Influence of Crisis Communication Strategies on Public Perception of Organisations: A Study of Caleb University - Adeyemi, Adefisola; Falobi, Funmi; Akin-Odukoya, Omolara; Onyejelem, Timothy Ekeledirichukwu; Ridwan, Muhammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Effective crisis communication plays a crucial role in preserving an organization’s reputation during significant national or even internal crises in the organisation. This study investigates the impact of crisis communication strategies on the public perception of an organization, focusing on Caleb University. The research delves into how effective crisis communication practices influence how the public views an organization during challenging times. By analysing the specific strategies employed by Caleb University in managing crises and their subsequent effects on public perception, this study aims to provide valuable insights into the importance of communication strategies in shaping public opinion and maintaining organizational reputation. In this study, the positivist approach of research design was adopted, which informed the choice of survey method. Questionnaire was used as an instrument of data collection. The population of the study consist of students in the Department of Mass Communication, Caleb University from which a sample of 200 respondents were drawn based on the principle of stratified sampling. The findings of this study revealed that there is a positive influence of crisis communication on the public perception of crisis events and illustrates that adopting effective crisis communication strategies during crises delivers improved outcomes. The study concludes that Effective crisis communication at Caleb University would rely on preemptive planning, clear and transparent messaging, a designated crisis response team, and continuous engagement with all stakeholders.